Inkjet-printing of 3D optical systems - Kemper, Falk; Reif, Maximilian; Wolleb, Sabrina J.; Schönfelder, Thomas; Pohle, Lisa; Beckert, Erik; Schulz, Ulrike; Tünnermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
The contribution describes the inkjet printing of 3D-optical components and systems, based on the hybrid polymer ORMOCER®, which exhibits not only good optical, but also excellent stability parameters versus environmental conditions such as temperature or radiation. With repeating the printing and UV-curing of single printed layers multiple times, a 3D-shape is formed out of thousands of individual layers. To increase the transmission of the 3D-printed optics a tailored AR-plas® one-step plasma treatment was developed. By varying the plasma parameters, the increase of transmission can be tailored within the whole visible spectrum and thus the overall transmission can be increased from 90% to more than 97%. This ensures the additive manufacturing of individualized 3D-optics with very high performance.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 3D-printing; Anti-reflective; Freeform optics; Hybrid polymer; Inkjet; Optics; Ormocer